GO-NGO collaboration in health sector management of Bangladesh: an evaluation of BRAC’s health programme - Maruf, Md. Hasan (BRAC University, 2014)
This thesis is submitted in partial fulfillment of the requirements for the degree of Masters of Arts in Governance and Development, 2013.